Numerical analysis of lime stabilized capping under embankments based on expansive subgrades - Manoj Anaokar; Sharad Mhaiskar (Heliyon, 2019)
This paper investigates the efficacy of an alternative construction methodology proposed by the authors in the form of a ‘C’-shaped lime stabilized capping. It is used for confining expansive clay subgrade soil under embankments carrying flexible pavement at their top, to enhance their performance. The role of capping in controlling moisture ingress responsible for swelling is assessed by studying vertical displacements and suctions in expansive subgrade soils. The load-displacement behavior and the variations in suctions of expansive subgrade soil are studied by using Mohr-Coulomb material model and Van Genuchten Hydraulic Model respectively in FEM based Software PLAXIS 3D. It is observed from the results that; the swelling displacements are considerably reduced and suctions under embankment toe are observed to increase. It can therefore be concluded that, the lime stabilized capping consisting of horizontal buffer layer and vertical cut-offs is effective in controlling swelling displacements in expansive subgrades.